PREOPERATIVE ASSESSMENT FOR NON-SMALL-CELL LUNG CANCER SURGERY - Stevanović, Stefan (Acta medicae Medianae, 2026)
Lung cancer is the most common malignant tumor and globally the leading cause of death from malignant diseases in the general population, accounting for approximately 25% of all cancer deaths. According to current data, approximately 7,000 people are diagnosed with lung cancer in Serbia annually, and about 5,000 die from the disease. Treatment for lung cancer is complex and multidisciplinary, with surgery playing a central role in stages I to III-A. Despite numerous studies confirming that surgical resection offers the best chance of recovery, only 20–30% of patients are eligible for surgery at the time of diagnosis. There are many reasons for this, including advanced disease, comorbidities, weakened respiratory function, and poor performance status. Considering that surgical lung resections are often accompanied by peri- and postoperative complications, a detailed preoperative risk assessment is crucial for determining the outcome of treatment. The remainder of this text will outline the currently valid guidelines and protocols for preoperative risk assessment, with a particular focus on high-risk patients (elderly, smokers, chronic obstructive pulmonary disease—COPD—patients, and obese individuals). It will also delve into the role of spirometric-diffusion parameters and stress tests in this assessment.